Timing of Rebleeding in High-Risk Peptic Ulcer Bleeding after Successful Hemostasis: A Systematic Review - Sara El Ouali; Alan N Barkun; Myriam Martel; Davide Maggio (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Peptic ulcer rebleeding (PUR) usually occurs within three days following endoscopic hemostasis. However, recent data have increasingly suggested delayed rebleeding.